Can someone help me solving this differential equation?
Find the general solution of [tex]x^4y''+x^3y'-4x^2y=1 given tha [tex]t y_1=x^2 is a solution of the associated homogeneous equation.

Respuesta :

Use reduction of order. Given a solution [tex]y_1(x) = x^2[/tex], look for a second solution of the form [tex]y_2(x) = y_1(x)v(x)[/tex].

Compute the first two derivatives of [tex]y_2(x)[/tex]:

[tex]y_2 = x^2v \\\\ {y_2}' = x^2v' + 2xv \\\\ {y_2}'' = x^2v''+4xv' + 2v[/tex]

Substitute them into the ODE:

[tex]x^4 (x^2v'' + 4xv' + 2v) + x^3 (x^2v' + 2xv) - 4x^2 (x^2v) = 1 \\\\ x^6v'' + 5x^5v' = 1[/tex]

Now substitute [tex]w(x) = v'(x)[/tex] and you end up with a linear ODE:

[tex]x^6w'+5x^5w=1[/tex]

Multiply through both sides by [tex]\frac1x[/tex] (if you're familiar with the integrating factor method, this is it):

[tex]x^5w'+5x^4w = \dfrac1x[/tex]

Bear in mind that in order to do this, we require [tex]x\neq0[/tex]. Just to avoid having to deal with absolute values later, let's further assume [tex]x>0[/tex].

Notice that the left side is the derivative of a product,

[tex]\left(x^5w\right)' = \dfrac1x[/tex]

Integrate both sides with respect to [tex]x[/tex] :

[tex]x^5w = \displaystyle \int\frac{\mathrm dx}x \\\\ x^5w = \ln(x) + C_1[/tex]

Solve for [tex]w(x)[/tex] :

[tex]w = \dfrac{\ln(x)+C_1}{x^5}[/tex]

Solve for [tex]v(x)[/tex] by integrating both sides:

[tex]v = \displaystyle \int \frac{\ln(x)+C_1}{x^5} \,\mathrm dx[/tex]

Integrate by parts:

[tex]\displaystyle f = \ln(x) + C_1 \implies \mathrm df = \frac{\mathrm dx}x \\\\ \mathrm dg = \frac{\mathrm dx}{x^5} \implies g = -\frac1{4x^4} \\\\ \implies v = -\frac{\ln(x)+C_1}{4x^4} + \frac14 \int \frac{\mathrm dx}{x^5} \\\\ v = -\frac{\ln(x)+C_1}{4x^4} - \frac1{16x^4} + C_2 \\\\ v = -\frac{4\ln(x)+C_1}{16x^4}+C_2[/tex]

Solve for [tex]y_2(x)[/tex] :

[tex]\displaystyle \frac{y_2}{x^2} = -\frac{4\ln(x)+C_1}{16x^4}+C_2 \\\\ y_2 = -\frac{4\ln(x)+C_1}{16x^2} + C_2x^2[/tex]

But since [tex]y_1(x)=x^2[/tex] is already accounted for, the second solution is just

[tex]\displaystyle y_2 = -\frac{4\ln(x)+C_1}{16x^2}[/tex]

Still, the general solution would be

[tex]\displaystyle \boxed{y(x) = -\frac{4\ln(x)+C_1}{16x^2} + C_2x^2}[/tex]

ACCESS MORE